Management Accounting Practices In Decision Making In Islamic Boarding Schools - Humaidi; Umi Muawanah; Oyong Lisa (Universitas Muhammadiyah Malang, 2025)
Research Objectives: This research intends to analyze the influence of management accounting practices on strategic decision making in Islamic boarding schools located in Jombang, with a focus on the cost allocation system, budgeting system, and performance evaluation. Method/Approach: This research employs a quantitative method with a survey approach. The research population consists of Islamic boarding school managers, with a sample size of 47 respondents selected using purposive sampling techniques. A questionnaire designed based on relevant management accounting aspects was utilized for data collection. Data analysis was conducted through using descriptive statistical techniques. Results: The findings of the research reveal that the implementation of management accounting practices, including costing systems, budgeting systems, and performance evaluations, have a significant impact on strategic decision making in Islamic boarding schools. The quality of information systems is also proven to moderate the relationship between management accounting practices and strategic decision making, where Islamic boarding schools with better information systems can maximize the positive impact of these practices. Practice Implications: This study provides guidelines for Islamic boarding schools to improve financial management through the application of more modern management accounting practices, so as to increase transparency, accountability, and effectiveness in strategic decision making. Originality/Novelty: This study highlights the importance of integrating management accounting practices in the context of Islamic education, and shows how the quality of information systems can strengthen the relationship between accounting practices and strategic decision making.